2005
DOI: 10.1111/j.1745-6584.2005.0027.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of time‐space distributions of submarine ground water discharge

Abstract: Submarine ground water discharge (SGD) rates were measured continuously by automated seepage meters to evaluate the process of ground water discharge to the ocean in the coastal zone of Suruga Bay, Japan. The ratio of terrestrial fresh SGD to total SGD was estimated to be at most 9% by continuous measurements of electrical conductivity of SGD. Semidiurnal changes of SGD due to tidal effects and an inverse relation between SGD and barometric pressure were observed. Power spectrum density analyses of SGD, sea le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 33 publications
0
33
0
Order By: Relevance
“…This high estimate may have been an artifact of the shorter retention time of water at one location in the Sound (1.7 days), or elevated Ra in the coastal aquifer, possibly due to ingrowth under low-flow conditions. However, it is acknowledged that tidal pumping and wave set-up is able to generate vast fluxes of SGD from the aquifer so we cannot rule out the possibility of a high groundwater flux by means other than Darcy flow (Li et al, 1999;Taniguchi et al, 2002Taniguchi et al, , 2005. We report these minimum and maximum estimates to demonstrate the variability in calculated SGD that may result from a spatially variable marine and groundwater system.…”
Section: Submarine Groundwater Discharge (Sgd)mentioning
confidence: 87%
“…This high estimate may have been an artifact of the shorter retention time of water at one location in the Sound (1.7 days), or elevated Ra in the coastal aquifer, possibly due to ingrowth under low-flow conditions. However, it is acknowledged that tidal pumping and wave set-up is able to generate vast fluxes of SGD from the aquifer so we cannot rule out the possibility of a high groundwater flux by means other than Darcy flow (Li et al, 1999;Taniguchi et al, 2002Taniguchi et al, , 2005. We report these minimum and maximum estimates to demonstrate the variability in calculated SGD that may result from a spatially variable marine and groundwater system.…”
Section: Submarine Groundwater Discharge (Sgd)mentioning
confidence: 87%
“…FBM applied to coastal aquifers is contingent on the estimation (and prediction) of both aquifer recharge and submarine groundwater discharge; these are challenging to determine in the vast majority of circumstances (e.g. Scanlon et al 2002;Taniguchi et al 2006).…”
Section: Defining Fbm and Tlmmentioning
confidence: 99%
“…On the other hand, in water budgets of coastal aquifers, groundwater losses to the sea are not equal to SGD (the total outflow at the seaward aquifer boundary), since SGD contains not only the terrestrial groundwater but the recirculated water of marine origin as well. Studies concerning the relative contribution of SFGD and RSGD to the total SGD have been presented by Li et al (1999), Smith (2004) and Taniguchi et al (2005). Another study related to the problem is that of Smith and Turner (2001), who investigated the contribution of groundwater and recirculated surface water to an estuarine river.…”
Section: Introductionmentioning
confidence: 98%
“…For the particular conditions of the Swan-Canning Estuary, they found that RSGD c could be up to 35% of the total subsurface discharge to the river. Using water balance and material balance at the seabed of Suruga Bay, Japan, Taniguchi et al (2005) found that the portion of RSGD in SGD is more than 91%.…”
Section: Introductionmentioning
confidence: 99%